Man-Document : Week of Contemporary Art - Bany Starinna. - Lardeva, Galina; Linkov, Krassimir (Plovdiv : Banya Starinna, 1996)
Lardeva, Galina ; Popov, Philip ; Popov, Emil ; Daniel, Andrei ; Artinyan, Johannes ; Romenska, Monika ; Michell, Regula ; Bushy, Susan ; Genova, Nadya ; Mirazohiev, Emil ; Abadzhieva, Tanya ; Stoilov, Dimitar ; Ushev, Theodor ; Tiel, Verner ; Nedev, Bisser ; Mishev, Kolyo ; Penov, Tihomir ; Karamfilov, Kolyo ; Hranov, Atanas ; Damyanov, Krum ; Pavlov, Dimtcho ; Sluik, Ron ; Kurpershoek, Reinier ; Mihailova, Albena ; Dobrev, Krassimir
biografie
Man-Document : Week of Contemporary Art, Bany Starinna, Plovdiv, May 25 - 31, 1996
Engels & Bulgaars
boek